PENGARUH AKSESIBILITAS, DAYA TARIK WISATA, DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERKUNJUNG KE OBJEK WISATA DI KABUPATEN CILACAP - Aliya Alimi; Mukhroji Mukhroji (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the influence of influence of accessibility, tourist attraction, digital marketing and service quality on the decision to visit tourist attractions in Cilacap Regency. The phenomenon driving this research is the fluctuation in the number of visits to tourist attractions in Cilacap Regency over the past five years. This study employs a quantitative approach with a non-probability sampling technique using convenience sampling. Data were collected through questionnaires distributed to 270 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) with the SmartPLS program to test the direct influence among variables. The results of the analysis show that: 1) accessibility has a positive effect on visiting decisions, 2) tourist attraction has a positive effect on visiting decisions, 3) digital marketing has a positive effect on visiting decisions, 4) service quality has a positive effect on visiting decisions. The findings of the study contribute to the development of theory and provide practical recommendations for tourism managers in efforts to enhance competitiveness and increase tourist visits in Cilacap Regency